S-Nitrosylation of Calcium-Handling Proteins in Cardiac Adrenergic Signaling and Hypertrophy. Issue 9 (9th October 2015) - Irie, Tomoya; Sips, Patrick Y.; Kai, Shinichi; Kida, Kotaro; Ikeda, Kohei; Hirai, Shuichi; Moazzami, Kasra; Jiramongkolchai, Pawina; Bloch, Donald B.; Doulias, Paschalis-Thomas; Armoundas, Antonis A.; Kaneki, Masao; et al.
Abstract : Rationale: : The regulation of calcium (Ca 2+ ) homeostasis by β-adrenergic receptor (βAR) activation provides the essential underpinnings of sympathetic regulation of myocardial function, as well as a basis for understanding molecular events that result in hypertrophic signaling and heart failure. Sympathetic stimulation of the βAR not only induces protein phosphorylation but also activates nitric oxide–dependent signaling, which modulates cardiac contractility. Nonetheless, the role of nitric oxide in βAR-dependent regulation of Ca 2+ handling has not yet been explicated fully. Objective: : To elucidate the role of protein S-nitrosylation, a major transducer of nitric oxide bioactivity, on βAR-dependent alterations in cardiomyocyte Ca 2+ handling and hypertrophy. Methods and Results: : Using transgenic mice to titrate the levels of protein S-nitrosylation, we uncovered major roles for protein S-nitrosylation, in general, and for phospholamban and cardiac troponin C S-nitrosylation, in particular, in βAR-dependent regulation of Ca 2+ homeostasis. Notably, S-nitrosylation of phospholamban consequent upon βAR stimulation is necessary for the inhibitory pentamerization of phospholamban, which activates sarcoplasmic reticulum Ca 2+ -ATPase and increases cytosolic Ca 2+ transients. Coincident S-nitrosylation of cardiac troponin C decreases myocardial sensitivity to Ca 2+ . During chronic adrenergic stimulation, global reductions in cellular S-nitrosylation mitigate hypertrophic signaling resulting from Ca 2+ overload. Conclusions: : S-Nitrosylation operates in concert with phosphorylation to regulate many cardiac Ca 2+ -handling proteins, including phospholamban and cardiac troponin C, thereby playing an essential and previously unrecognized role in cardiac Ca 2+ homeostasis. Manipulation of the S-nitrosylation level may prove therapeutic in heart failure. Abstract : Supplemental Digital Content is available in the text.